2010
DOI: 10.20467/1091-5710.14.1.44
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of Persons with Life-Sustaining Cardiac Devices

Abstract: The purpose of this study was to describe the experience of persons with permanent implantable cardiac devices. Purposeful sampling was by snowball method. Seven participants met the selection criteria with only three completing the data generation procedure. Interviews were guided by semistructured questions, conducted via the telephone, and electronically recorded. Van Manen’s (1990) phenomenological approach was used to analyze the data. Four thematic categories were identified: Longing and Loneliness, Depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the study by Locsin et al . (), they found that the experience of persons with life sustaining cardiac devices in the USA was that the patients desired a new life. After the implantation of a pacemaker, the patients described themselves as ‘having a new lease on a new life’ (p. 48).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Locsin et al . (), they found that the experience of persons with life sustaining cardiac devices in the USA was that the patients desired a new life. After the implantation of a pacemaker, the patients described themselves as ‘having a new lease on a new life’ (p. 48).…”
Section: Discussionmentioning
confidence: 99%